The Influence Of Transformational Leadership, Job Satisfaction And Flexible Working Arrangement On Turnover Intention In X Life Insurance Company In Indonesia - Vina S Marinda; Indra T Anggapradja (UNIVED Press, 2024)
This research aims to find out how transformational leadership, job satisfaction and flexible working arrangements influence turnover intention at Life Insurance Company X in Indonesia. This research uses quantitative research methods and explanatory research, involving 100 employees as samples who are marketing agents at Life Insurance Company X in Indonesia. This research uses a purposive sampling technique. In collecting data, this research used questionnaire distribution. The results of this research show that transformational leadership, job satisfaction and flexible working arrangements have a significant effect on Turnover Intention at X Life Insurance Company in Indonesia. transformational leadership, job satisfaction and flexible working arrangements have a proportion of influence on Turnover Intention of 94.8% while the remaining 5.2% is influenced by other variables that are not in the research model. To reduce turnover intention, transformational leadership, job satisfaction and flexible working arrangements need to be managed and realized well